2013
DOI: 10.1371/journal.pone.0057426
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-Dependent Role for Cold-Inducible RNA Binding Protein in Regulating Interleukin 1β

Abstract: The cold inducible RNA binding protein (CIRBP) responds to a wide array of cellular stresses, including short wavelength ultraviolet light (UVC), at the transcriptional and post-translational level. CIRBP can bind the 3'untranslated region of specific transcripts to stabilize them and facilitate their transport to ribosomes for translation. Here we used RNA interference and oligonucleotide microarrays to identify potential downstream targets of CIRBP induced in response to UVC. Twenty eight transcripts were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 54 publications
1
44
0
Order By: Relevance
“…4 and 5). A recent study reported the involvement of Cirp in regulating expression of IL1b, another NF-kB target gene, in cultured fibroblasts (44). In bone marrow-derived macrophages, IL1b mRNA level was decreased in the absence of Cirp (data not shown).…”
Section: Discussionmentioning
confidence: 82%
“…4 and 5). A recent study reported the involvement of Cirp in regulating expression of IL1b, another NF-kB target gene, in cultured fibroblasts (44). In bone marrow-derived macrophages, IL1b mRNA level was decreased in the absence of Cirp (data not shown).…”
Section: Discussionmentioning
confidence: 82%
“…UV light led to increased expression of five transcripts in a CIRBP-dependent manner. The three largest responders encoded inflammatory cytokines (15). The induction of these cytokines did not depend on a direct interaction of CIRBP with the 3¢UTRs of these mRNAs.…”
Section: Uv Light Increases the Stability Of Specific Transcriptsmentioning
confidence: 89%
“…Therefore, transcriptional changes can give rise to secondary alterations in gene expression. For example, cold inducible RNA binding protein (CIRBP) is post-transcriptionally modified, and its expression can be increased in response to many cellular stresses, including UV light (15,164). This protein can protect specific mRNAs from degradation (ATR and CLOCK, for example), shuttle them to the cytoplasm, and stimulate translation of the encoded proteins (116,166).…”
Section: Uv Light Increases the Stability Of Specific Transcriptsmentioning
confidence: 99%
See 2 more Smart Citations